2017
DOI: 10.3389/fmicb.2017.02200
|View full text |Cite|
|
Sign up to set email alerts
|

Characterization of Metagenomes in Urban Aquatic Compartments Reveals High Prevalence of Clinically Relevant Antibiotic Resistance Genes in Wastewaters

Abstract: The dissemination of antimicrobial resistance (AMR) is an escalating problem and a threat to public health. Comparative metagenomics was used to investigate the occurrence of antibiotic resistant genes (ARGs) in wastewater and urban surface water environments in Singapore. Hospital and municipal wastewater (n = 6) were found to have higher diversity and average abundance of ARGs (303 ARG subtypes, 197,816 x/Gb) compared to treated wastewater effluent (n = 2, 58 ARG subtypes, 2,692 x/Gb) and surface water (n = … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
73
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
3
3
1

Relationship

2
5

Authors

Journals

citations
Cited by 94 publications
(81 citation statements)
references
References 59 publications
(73 reference statements)
8
73
0
Order By: Relevance
“…In total, 38 libraries and one negative control library using Illumina TruSeq Nano DNA Library Kit were constructed. The sequencing libraries with a corresponding insert size and adapters were prepared accordingly as previously described (Ng et al, 2017). The Illumina's PhiX control library was used as standard.…”
Section: Random Amplification and Sequencing Of Viromesmentioning
confidence: 99%
“…In total, 38 libraries and one negative control library using Illumina TruSeq Nano DNA Library Kit were constructed. The sequencing libraries with a corresponding insert size and adapters were prepared accordingly as previously described (Ng et al, 2017). The Illumina's PhiX control library was used as standard.…”
Section: Random Amplification and Sequencing Of Viromesmentioning
confidence: 99%
“…Different non-overlapping paths on the Figure 4 represents several different families of bla CTX−M gene: green corresponds to CTX-M-15 family, while blue and red corresponds to CTX-M-9 and CTX-M-14 respectively (differs from each other only by 2 SNPs). Note that Table S5 in [12] mentiones the presence of CTX-M-15 and CTX-M-18 beta-lactamase families in this dataset, however we found that the extracted graph path that corresponds to CTX-M-9 aligned to the Fig. 5.…”
Section: Urban Wastewater Metagenomementioning
confidence: 74%
“…In [12] comparative metagenomics was used to investigate the occurrence of antibiotic resistant genes in wastewater and urban surface water environments in Singapore. For this experiment we took H1 (clinical isolation ward, SRA acc.…”
Section: Urban Wastewater Metagenomementioning
confidence: 99%
See 1 more Smart Citation
“…A metagenomic characterization study found bla NDM-1 in hospital wastewater, indicating wastewaters as a hotspot for ARGs. 43 An important aspect of understanding and combating the rising prevalence of antibiotic resistance is to survey and monitor environmental reservoirs for infectious agents and accumulation of ARGs. The human microbiome is regularly exposed and influenced by environmental bacteria.…”
Section: Using Metagenomics To Monitor Environmental and Biological Rmentioning
confidence: 99%